(untitled) (Human Factors in Design, 2022)
This research presents a framework for designing persuasive mobile healthcare applications. The aim of the proposed framework is to help the analysis and design of mobile healthcare apps. Two versions of the framework are presented. A study was conducted with experts in order to test the framework and also to provide suggestions for it. The test with the experts showed that the framework was able to help identify the strengths and weaknesses of the applications and proved to be effective. It is expected that the proposed framework will help designers and programmers to design and analyse mobile applications with a persuasive character, and thus assist users in changing and maintaining healthy behaviour.